Key Factors for Thymic Function and Development - Shichkin, Valentin P.; Antica, Mariastefania (Frontiers in Immunology, 2022)
The thymus is the organ responsible for T cell development and formation of the adaptive immunity function. Its multicellular environment consists mainly of the different stromal cells and maturing T lymphocytes. Thymus specific progenitors of epithelial, mesenchymal, and lymphoid cells with stem cell properties represent only minor populations. The function of the thymus is predominantly determined by the thymic stromal structure. The stromal components, mostly epithelial and mesenchymal cells form this specialized area and they mainly support the consistent developmental program of functionally distinct conventional T cell subpopulations, such as the MHC restricted single positive CD4+ CD8- and CD4- CD8+ cells, and regulatory T lymphocytes (Foxp3+) as well as the formation of innate natural killer T cells (iNKT) and γδT cells. A number of physiological causes comprising stress and aging as well as iatrogenic factors like thymectomy and chemo/radiotherapy can harm the thymus function. The present review recapitulates our knowledge of the development and function of the thymus with a focus on thymic epithelial cells as well as other stromal components, the signaling and transcriptional pathways underlying the intrathymic cell interaction, which are significant for T cell differentiation and for restoring the thymic function after damage to reach the therapeutic benefits.